Penggunaan Film Pendek Sebagai Bentuk Branding PT Sarinah - Ignatius Dwi Rezky Joel; Uud Wahyudin; Dedi Rumawan Erlandia (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
This research was conducted to find out the message producer meaning towards PT Sarinah's branding in the short film "Mbok dan Bung", the audience reception towards PT Sarinah's branding in the short film "Mbok dan Bung", and the audiences reading position towards the use of the short film "Mbok dan Bung" as PT Sarinah's branding which positioned using the Stuart Hall encoding/decoding model. The method used is qualitative reception analysis with observation and interview data collection techniques. The results of the study show that the message producer meaning of PT Sarinah's branding in the short film "Mbok dan Bung" is divided into four branding scenes that contain the humanity values, gender equality values, historical values, and innovation values implemented by PT Sarinah. The audience's reception for the branding of the four scenes received various interpretations from the audience, but in the end the audience, who are movie observers, stated the branding that PT Sarinah wanted to create in the short film "Mbok dan Bung" had been successful.Â  The audience reading position of the four branding scenes has various audience reading positions, in the first scene there are Dominant Hegemonic audience reading positions as the majority and Oppositional Hegemonic Reading, in the second scene there are Dominant Hegemonic audience reading positions as the majority and Oppositional Hegemonic Reading, in the third scene there are audience reading positions that are balanced on Dominant Hegemonic and Oppositional Hegemonic Reading, in the fourth scene there are Dominant Hegemonic audience reading positions as the majority, Negotiated Reading, and Oppositional Hegemonic Reading.